Di-μ2-chlorido-bis[chlorido(η5-2,3,4,5-tetramethyl-1-propylcyclopentadienyl)iridium(III)] - Nicholas De Weerd; David Morris; Joseph S. Merola (Acta Crystallographica Section E, 2013)
The asymmetric unit of the title complex, [Ir2Cl4(C12H19)2], a versatile starting material for the preparation of uniquely substituted pentaalkylcyclopentadienyl–iridium complexes, consists of an iridium(III) atom, a substituted cyclopentadienyl ligand and two chlorine ligands. The full dimer is generated by an inversion center. In the dimer, the two IrIII atoms and two bridging Cl atoms form a perfectly planar ring. The two IrIII atoms and the two terminal Cl atoms also form a rigorous plane that is orthogonal [89.48 (3)°] to the Ir2Cl2 ring. The plane of the cyclopentadienyl ligand forms a dihedral angle of 54.06 (7)° with respect to the Ir2Cl2 ring.